The ARSQ 2.0 reveals age and personality effects on mind-wandering experiences - Diaz, B. A.; Van Der Sluis, Sophie; Benjamins, Jeroen S.; Stoffers, Diederick; Hardstone, Richard; Mansvelder, Huibert D.; Van Someren, Eus J.; Linkenkaer-Hansen, Klaus (Frontiers in Psychology, 2014)
The human brain frequently generates thoughts and feelings detached from environmental demands. Investigating the rich repertoire of these mind-wandering experiences is challenging, as it depends on introspection and mapping its content requires an unknown number of dimensions. We recently developed a retrospective self-report questionnaire—the Amsterdam Resting-State questionnaire (ARSQ)—which quantifies mind wandering along seven dimensions: “Discontinuity of Mind”, “Theory of Mind”, “Self”, “Planning”, “Sleepiness”, “Comfort”, and “Somatic Awareness”. Here, we show using confirmatory factor analysis that the ARSQ can be simplified by standardizing the number of items per factor and extending it to a 10-dimensional model, adding “Health Concern”, “Visual Thought” and “Verbal Thought”. We will refer to this extended ARSQ as the “ARSQ 2.0”. Testing for effects of age and gender revealed no main effect for gender, yet a moderate and significant negative effect for age on the dimensions of “Self”, “Planning” and “Visual Thought”. Interestingly, we observed stable and significant test-retest correlations across measurement intervals of 3 to 32 months except for “Sleepiness” and “Health Concern”. To investigate whether this stability could be related to personality traits, we correlated ARSQ scores to proxy measures of Cloninger’s Temperament and Character Inventory, revealing multiple significant associations for the trait “Self-Directedness”. Other traits correlated to specific ARSQ dimensions, e.g., a negative association between “Harm Avoidance” and “Comfort”. Together, our results suggest that the ARSQ 2.0 is a promising instrument for quantitative studies on mind wandering and its relation to other psychological or physiological phenomena.